The Role of Sanad Studies in Ensuring the Authenticity of Mu'allaq Balaghât Hadiths in the Book of Muwatta' Malik - Hafizzullah; Sepri Aulia; Dewi Putri (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2023)
One of the separate studies in hadith scholarship is Imam Malik's narration model using sighat tahammul which is different from other scholars. That is with the hadiths balâghât (hadiths beginning with